PENGARUH EPS, PROCEEDS, SERTA REPUTASI UNDERWRITER TERHADAP UNDERPRICING - Aningtya, Raisa; Jubaedah, Jubaedah (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study was conducted to prove the influence of eps, proceeds, and underwriter reputation to the underpricing in companies doing an IPO (Initial Public Offering) in the period from 2011 to 2013. The study use secondary data obtained from Indonesian Stock Exchange (ISE) website and the annual financial statements that audited and published. Population in this research is Initial Public Offering (IPO) companies listed in Indonesian Stock Exchange (ISE) in the period 2011-2013. Sampling technique using purposive sampling method, and obtained a sample 0f 60 IPO and Underpricing companies. Data analysis technique use is multiple linear regression analysis. Hypotesis testing is done by using the F test statistics and t test statistics with a confidence level of 5%. The results showed that EPS, Proceeds, Underwriter Reputation simultaneously influence on Underpricing. Then, the results showed that only Proceeds has negative influence on Undepricing. While Earning Per Share (EPS) and Underwriter Reputation has no influence on Underpricing.